2021
DOI: 10.21809/rilemtechlett.2021.142
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of multi-layer 3D concrete printing

Abstract: This paper presents a computational fluid dynamics model fit for multi-layer 3D Concrete Printing. The numerical model utilizes an elasto-visco-plastic constitutive model to mimic the flow behaviour of the cementitious material. To validate the model, simulation data is compared to experimental data from 3D printed walls. The obtained results show that the numerical model can reproduce the experimental results with high accuracy and quantify the extrusion load imposed upon the layers. Such load is found to exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Numerical methods have been helpful in advancing our understanding of the printing process (Perrot et al, 2021;Khan and Koç, 2022). A number of studies have demonstrated the efficacy of these methods in accurately replicating experimental results (Comminal et al, 2020;Liu et al, 2020;Spangenberg et al, 2021). Liu et al attributed discrepancies between numerical and experimental results to variations in flow rate and minor changes in rheological properties post-pumping (Liu et al, 2020).…”
Section: Numerical Modelingmentioning
confidence: 99%
“…Numerical methods have been helpful in advancing our understanding of the printing process (Perrot et al, 2021;Khan and Koç, 2022). A number of studies have demonstrated the efficacy of these methods in accurately replicating experimental results (Comminal et al, 2020;Liu et al, 2020;Spangenberg et al, 2021). Liu et al attributed discrepancies between numerical and experimental results to variations in flow rate and minor changes in rheological properties post-pumping (Liu et al, 2020).…”
Section: Numerical Modelingmentioning
confidence: 99%
“…Note that in Eqs. (19) and (20) we made use of the expression , which holds for any invertible tensor A. The updated elastic deformation gradient and the updated elastic left Cauchy-Green deformation tensor are found from Eqs.…”
Section: Thermodynamic Consistencymentioning
confidence: 99%
“…When printing multiple layers, the shapes, the deformations, and the contact forces acting on the substrate, were previously analyzed in Refs. [15,[18][19][20][21][22]. According to the computational and experimental study in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In complement to the physical printing, CFD modelling is able to reproduce the extrusion-deposition of the printable concrete and investigate some specific constraints to the physical print [19][20][21][22]. The angular toolpath planning in 3DCP is in its infancy.…”
Section: Introductionmentioning
confidence: 99%